Correlation of Nature of Amniotic Fluid with Maternal Risk on Neonatal Outcome at GMC, Ratlam - Devendra Nargawe; Manish Rathore (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: After taking ethical clearance from hospital ethical board, this prospective study is being conducted at Govt. Medical College, Ratlam with a sample size of 149. All newborn babies born through MSAF will be included. Relevant history, clinical examination and relevant investigations would be done. Subjects and Methods: This prospective study is being conducted from 01/06/2016 to 01/6/2017 at Govt. Medical College, Ratlam with a sample size of 149. All newborn babies born through MSAF will be included. Relevant history, clinical examination and relevant investigations would be done. Results: Average number of maternal risk factors is 18(12%); of which 9 cases(6.82%) belong to thin MSL and 9 cases (50%) belong to thick MSL. The mean difference between two groups is statistically significant (p value= .000). It comprises: PIH-13 cases (8.67%) of which 5 cases (3.79%) are thin MSL and 8 cases (44.4%) belong to thick MSL; Oligohydraminos-3 cases (2%),all 3 cases (2.27%) are from thin MSL and 0 case from thick MSL;GDM-2 cases(1.34%),thin MSL comprises 1 case(0.76%) and thick MSL comprises 1 case (5.55%). Conclusion: Meconium stained liquor is more commonly associated with PIH, post-datism, oligohydroamnios and DM, etc. Risk factors which were associated with MSAF were PIH in 8.67%, oligohydramnios in 2% of the cases, GDM in 1.34% cases. (p value= .000),which is significant.